Введение в аналитическую механику - Беленький Илья Маркович (Высшая школа, 1964)
Экземпляры: КХ (20120920) / Инвентарный номер: 367065 / Цена: 0.51 / Сис.шифр: 531 / Авт.знак: Б 43 / ГРНТИ: 30 / ББК: 22